Sludge production from municipal wastewater treatment in sewage treatment plant. Issue 10 (19th May 2017) - Demirbas, Ayhan; Edris, Gaber; Alalayah, Walid M.
ABSTRACT: Sewage sludge is obtained from wastewater treatment in sewage treatment plants. The sludge consists of two basic forms, sludge and secondary sludge, also known as activated sludge in the case of activated sludge process. Municipal sewage sludge (MSS) or only sewage can be a solid, semi-solid, or liquid muddy residue. It contains mainly proteins, sugars, detergents, phenols, and lipids and also includes toxic and hazardous organic and inorganic pollutants source. Sewage is a mixture of domestic and industrial wastes that contains above 99% water. It is produced by residential, institutional, commercial, and industrial establishments. Sludge is semi-solid slurry and can be produced as sewage sludge from wastewater treatment processes. The sludge consists of a wide range of harmful substances such as dioxins and furans, polychlorinated biphenyls, organochlorine pesticides, absorbed and extracted chlorine derivatives, polycyclic aromatic hydrocarbons, phenols and their derivatives, phthalate, and others. Sewage treatment is the process of removing contaminants from wastewater, primarily from household sewage. It includes physical, chemical, and biological processes to remove these contaminants and produce environmentally safe treated wastewater. The treatment is divided into three stages: pretreatment, primary treatment, and secondary treatment. In pretreatment, large solids and grit are removed by screening. In primary treatment, the water is left to stand so that solids can sink to the bottom and oil and grease can rise to the surface. In secondary treatment, the sludge is further treated in sludge digesters.